Religion, virtues, and health: new directions in theory construction and model development - Krause, Neal Miller (Oxford University Press, 2022)
"The literature on the relationship between religion and health is vast, but it is in a state of disarray. One empirical study has been piled upon another while little effort has been made to integrate them into a more tightly knit theoretical whole. This book was designed to address this problem. It is the product of forty years of empirical research, hundreds of peer-reviewed publications, and countless hours of deep reflection. This volume contributes to the literature in three ways: (1) a unique approach to theory construction and model development is presented that is designed to produce a conceptual scheme that is evidence based and empirically verifiable; (2) a new construct - communities of faith - that has largely been overlooked in empirical studies on religion is introduced; and (3) the need is highlighted for a no-holds barred discussion of how to practice one's research craft"--